The HOVON68 CLL trial revisited: performance status and comorbidity affect survival in elderly patients with chronic lymphocytic leukemia. Issue 3 (4th March 2017) - Vojdeman, Fie Juhl; van't Veer, Mars B.; Tjønnfjord, Geir E.; Itälä-Remes, Maija; Kimby, Eva; Polliack, Aaron; Wu, Ka L.; Doorduijn, Jeanette K.; Alemayehu, Wendimagegn G.; Wittebol, Shulamiet; Kozak, Tomas; Walewski, Jan; et al.
Abstract: In the HOVON68 CLL trial, patients 65 to 75 years of age had no survival benefit from the addition of low-dose alemtuzumab to fludarabine and cyclophosphamide (FC) in contrast to younger patients. The reasons are explored in this 5-year trial update using both survival analysis and competing risk analysis on non-CLL-related mortality. Elderly FCA patients died more frequently from causes not related to CLL, and more often related to comorbidity (mostly cardiovascular) than to infection. In a Cox multivariate analysis, del(17p), performance status >0, and comorbidity were associated with a higher non-CLL-related mortality in the elderly independent of the treatment modality. Thus, while the 'fit' elderly with no comorbidity or performance status of 0 might potentially benefit from chemo-immunotherapy with FC, caution is warranted, when considering alemtuzumab treatment in elderly patients with cardiovascular comorbidity.